Numerical investigation of rub-induced composite fan blade vibrations and abradable coating removals. (15th October 2019) - Xiao, Jia-Guang-Yi; Chen, Yong; Tian, Jie; Ou-Yang, Hua; Wang, Anjenq
Abstract: Composite blade vibrations, removal of abradable coating, and blade stress resulting from blade/casing rubs are investigated. Composite fan blade models with different stacking sequences and a metal blade are created and calculated through a three-dimensional finite element method. Centrifugal stiffness, damping of composite structures, B-spline surfaces, and abradable coating are included in the calculations. The results show that the maximum vibration amplitudes of composite blades at different rotational speeds could be affected by stacking sequences. The responses of metal blade are more sensitive to the natural frequencies of the second to the fifth blade modes than those of the composite blades. Abradable coating removals are highly related to blade vibration amplitudes. Considerably more coatings are removed by the metal blade than by the composite blades at the design speed, particularly in the axial direction. Moreover, according to the stress results, the metal blade is more vulnerable to rub-induced vibrations than the composite blades at the design speed. Larger vibration amplitudes in the composite blades do not necessarily lead to lower failure margins because of the complexity of composite structures. The strategy established can be utilized to aid in the initial designs of state-of-the-art composite blades and reduce potential rub-induced problems.